2016
DOI: 10.1021/acsmedchemlett.6b00224
|View full text |Cite
|
Sign up to set email alerts
|

Diverging Novobiocin Anti-Cancer Activity from Neuroprotective Activity through Modification of the Amide Tail

Abstract: Novobiocin is a natural product that binds the Hsp90 C-terminus and manifests Hsp90 inhibitory activity. Structural investigations on novobiocin led to the development of both anti-cancer and neuroprotective agents. The varied pharmacological activity manifested by these novobiocin analogs prompted the investigation of structure−function studies to identify these contradictory effects, which revealed that modifications to the amide side chain produce either anticancer or neuroprotective activity. Compounds tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Cell Culture and Transfection. The iHEK-P301L cells (32) and luciferaseexpressing PC3-MM2 cells (32) were cultured in DMEM supplemented with 10% FBS and 1% penicillin/streptomycin (Invitrogen). Inducible cells were incubated with 3 μg of tetracycline for 72 h. Forty-eight hours before harvest, transfections were performed with 2.5 μL of Lipofectamine 2000 (Invitrogen) per 1 μg of DNA, which was incubated in serum-free Opti-MEM for 5 min before adding the mixture drop-wise to the cells.…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture and Transfection. The iHEK-P301L cells (32) and luciferaseexpressing PC3-MM2 cells (32) were cultured in DMEM supplemented with 10% FBS and 1% penicillin/streptomycin (Invitrogen). Inducible cells were incubated with 3 μg of tetracycline for 72 h. Forty-eight hours before harvest, transfections were performed with 2.5 μL of Lipofectamine 2000 (Invitrogen) per 1 μg of DNA, which was incubated in serum-free Opti-MEM for 5 min before adding the mixture drop-wise to the cells.…”
Section: Methodsmentioning
confidence: 99%
“…1623 SAR studies revealed that the benzamide side chain is critical to manifest anti-proliferative activity and modifications to this moiety produced molecules that exhibited increased anti-proliferative activity against multiple cancer cell lines. 18, 2024 In addition, it was found that the noviose sugar could be replaced with ionizable amines, which resulted in analogues that showed improved potency and solubility. 2123, 25 In contrast, studies suggested that the coumarin core serves only as a backbone to orient the benzamide and sugar side chains in the binding pocket.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of KU-32 and KU-596 KU-32 was synthesized as previously described. 27 Briefly, acetic anhydride (0.02 mL, 0.21 mmol) was added to a solution of aniline (0.05 g, 0.13 mmol) in CH 2 Cl 2 (1 mL) at room temperature. After reaction completion as indicated by thinlayer chromatography, the solution was concentrated and purified via column chromatography (SiO 2 , 0-5% MeOH in CH 2 Cl 2 ) to afford the acetylated product as a white amorphous solid (0.05 g, 85% yield).…”
Section: Methodsmentioning
confidence: 99%
“…24,25 On the other hand, the novobiocin analogue KU-174 triggered client degradation and exhibited broad cytotoxicity, without inducing the heat shock response. 26 The ability of C-Hsp90 inhibitors to tune the functional outcomes of the Hsp90 chaperone cycle and exert differential therapeutic outcomes 27 makes them very attractive drug candidates against either different types of cancer or neurologic disorders. However, comprehensive mechanistic understanding of the mode of action of such ligands, as well as further rational SAR studies are hampered by the absence of structural or other experimental data characterizing their interaction with Hsp90.…”
Section: Introductionmentioning
confidence: 99%